Identification of novel canonical strigolactones produced by tomato - Wakabayashi, Takatoshi; Moriyama, Daisuke; Miyamoto, Ayumi; Okamura, Hironori; Shiotani, Nanami; Shimizu, Nobuhiro; Mizutani, Masaharu; Takikawa, Hirosato; Sugimoto, Yukihiro (Frontiers in Plant Science, 2022)
Canonical strigolactones (SLs), such as orobanchol, consist of a tricyclic lactone ring (ABC-ring) connected to a methylbutenolide (D-ring). Tomato plants have been reported to produce not only orobanchol but also various canonical SLs related to the orobanchol structure, including orobanchyl acetate, 7-hydroxyorobanchol isomers, 7-oxoorobanchol, and solanacol. In addition to these, structurally unidentified SL-like compounds known as didehydroorobanchol isomers (DDHs), whose molecular mass is 2 Da smaller than that of orobanchol, have been found. Although the SL biosynthetic pathway in tomato is partially characterized, structural elucidation of DDHs is required for a better understanding of the entire biosynthetic pathway. In this study, three novel canonical SLs with the same molecular mass as DDHs were identified in tomato root exudates. The first was 6,7-didehydroorobanchol, while the other two were not in the DDH category. These two SLs were designated phelipanchol and epiphelipanchol because they induced the germination of Phelipanche ramosa, a noxious root parasitic weed of tomato. We also proposed a putative biosynthetic pathway incorporating these novel SLs from orobanchol to solanacol.